O ensino da língua portuguesa nos cursos de graduação das ciências sociais aplicadas: a busca de sentido - Luciani, Luciana Paula Bento (2020)
Although the National Curricular Guidelines (DCN) do not require the teaching of the Portuguese language for the undergraduate courses in Business Management, Accounting and Economics, such subject is commonly included in their curricula. The DCN of these three courses specify the competences and skills that must be achieved, for students to have the oral and written communicative interaction expected for professional performance. Such competences and skills can certainly be enhanced with de mediation of the Portuguese Professor. Accordingly, the purpose of this dissertation is to investigate which communicative competences University Portuguese Professors must consider including in their planning and pedagogical-didactic actions, in order to foster the meaningful learning of the language, as well as the learners’ interest in the subject and the development of competences and skills directed towards communication, for the undergraduate students of the courses examined herein. With a view to analyzing the proposed problem, we used action-research as methodology. The study was carried out with graduates of a non-profit private institution of college education, located in the city of São Paulo. Furthermore, we analyzed 192 job advertisements, published in the social network LinkedIn, with the aim of verifying which communicative competences are professionally required from graduates of the areas considered herein. The theoretical framework of this dissertation is mainly based on pedagogical actions according to Paulo Freire (1994, 2000, 2001, 2014, 2015, 2016). We also used contributions of researchers who address teacher qualification and practice in the area of Language, meaningful learning and Applied Linguistics for the teaching of Portuguese. As a result, this dissertation produces knowledge of which communicative competences must be considered by University Portuguese Professors, in the teaching and learning process. Moreover, this research discusses how a subject, which is directed towards language studies, is essential for the comprehensive education of the graduates of the courses selected. Therefore, such subject is necessary for and pertinent to their respective curricula.